India’s lost rivers and rivulets - Borthakur, Anwesha; Singh, Pardeep (Joint Center on Global Change and Earth System Science of the University of Maryland and Beijing Normal University, 2016)
The manuscript highlights the tragedy of India’s extinct or near-extinct rivers and rivulets (i.e. very small rivers or streams) passing through some of the major Indian cities. These rivers were once considered healthy and sound systems supporting the population of a city by sustaining important sectors such as agriculture, pisciculture, transportation, industries, recreation among several others. Our motive is to attract attention of the scientific community, policymakers, government and non-governmental organizations and native dwellers towards this grave concern, where once sound ecosystems are today being damaged beyond the opportunity of rejuvenation. We have considered the instances of six Indian rivers and rivulets: the Bharalu and Bahini (Guwahati), Varuna and Assi (Varanasi) and Mula and Mutha (Pune). Today, most of these rivers are reduced to mere ‘nallahs’ or ‘sewers’ due to rapid, unplanned and haphazard developmental activities and urbanization processes ubiquitous in major Indian cities. For instance, River Assi in Varanasi is, today, almost no more. Encroachment is a common problem on all these river banks which results in extraordinary reduction in the width of the rivers and rivulets. As a consequence, the water flows to the banks of the rivers in no time even during a short rainfall episode. The deteriorating river systems in India pose major challenges to the sustenance of cities situated along them. Most of the pollution prevention initiatives by the central or the state governments are directed towards the major rivers such as the Ganga, practically ignoring the equally vital rivulets. Although local governments of most of these cities have undertaken initiatives to address the associated problems, the outcome of the same is highly dubious.
Keywords: Encroachment; India; Rivers; Rivulets; Water pollution